GELOMBANG REVOLUSI DAN TRANSISI POLITIK DI TIMUR TENGAH DAN AFRIKA UTARA* - Khamami Zada (SALAM: Jurnal Sosial dan Budaya Syar-i, 2015)
Abstract: Revolutionary Waves and Political Transition in Middle East and North Africa. Political transition in Tunisia has greatly influenced to neighboring countries, especially Egypt. Libya and Yemen have been disturbed by the government’s opposition. Political transition in Middle East is a fruit of authoritarian in which has been taking place since years ago. In addition, the high level of poverty gives effect to the transition process. Political transition in Tunisia and Egypt was happened in a peaceful way, marked by the resignation of Zain al-Din Ben Ali and Husni Mubarak. On the other hand, the armed conflict has been occurred in Libya and Yaman, heading the government’s loyalties and the opposition groups.  After the fall of Ben Ali and Husni Mubarak, it exist the struggle between radical groups and liberal ones in competing optical power.Key Words: political transition, revolution, Islamism, radicalism and liberalism Abstrak: Gelombang Revolusi dan Transisi Politik di Timur Tengah dan Afrika Utara. Efek domino transisi politik di Tunisia menjalar ke negara-negara tetangganya, terutama Mesir. Libya dan Yaman pun sedang menghadapi tuntutan mundur dari kelompok oposisi. Transisi politik di Timur Tengah dan Afrika Utara merupakan akibat dari otoritarianisme yang berlangsung lama dan tingginya kemiskinan. Transisi politik yang terjadi di Tunisia dan Mesir berlangsung dengan pola damai dengan mundurnya Zain al-Din Ben Ali dan Hosni Mubarak. Di tempat lain, Libya dan Yaman juga berlangsung konflik bersenjata antara kelompok yang setia terhadap pemerintah dan kelompok oposisi. Paska Ben Ali di Tunisia dan Mubarak di Mesir terjadi pertarungan antara kelompok Islamisme, radikalisme dan liberalisme dalam memperebutkan sumber politik kekuasaan dan kultural.Kata Kunci: transisi politik, revolusi, Islamisme, radikalisme, liberalisme  DOI: 10.15408/sjsbs.v2i1.224